PERTIMBANGAN KONSUMEN MEMILIH HOTEL ( Study Pada Konsumen Di Swiss-Belinn Ska Pekanbaru) - Ryan Bagus Wijaya; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Hospitality business is marketing in services. Bidangperhotelan effort at present shows the increasingly fierce competition dalamusaha increase occupancy rates were owned by each hotel. Untukitu entrepreneurs engaged in the hospitality business is required to bersaingagar can survive in this increasingly fierce competition. Jumlahwisatawan Increased domestic and foreign tourists as well as people who sedangberbisnis who need lodging services resulted in the growth of the hospitality businesses in Indonesia.This study fully address what factors considered by consumers choosing swiss yangmenjadi Belinn Pekanbaru hotel. This study uses a qualitative method to describe fully the idea of the consumer considerations chose this hotel.Likewise, the variables that affect keputusankonsumen stay at Swiss Belinn Ska Pekanbaru, who always considered olehpihak manajernen Hotel Swiss Belinn Ska Pekanbaru. In this study, consumers in deciding where to stay is influenced by location, fasilitsa, price and promodiKeywords: Consumer Consideration, Select Hotel, Swiss Belinn SKA